MONITORING DAYA PADA KURSI RODA CERDAS - Mubarok, Muhammad Aziz Nur; Suhendar, Suhendar; Anam, Khairul (Pusat Penelitian dan Pengabdian Masyarakat, 2024)
In an era of increasingly advanced technology, innovation in the field of sustainability and ease of mobility has become the main focus for improving the quality of life and independence for various groups of society, including people with disabilities. Intelligent wheelchairs are one example of a solution that has emerged to increase mobility and independence for savvy wheelchair users. This research aims to monitor the power of bright chairs to understand power consumption and energy use in developing intelligent wheelchairs. This test uses percent error data. The average results from calculating percent error data are relatively low. So, the current and voltage sensors are suitable for use in this percent error test. Tests were carried out with load and without load. In testing, the voltage and current required are the same. However, the speed produced by wheelchairs is different. When testing with a load, the wheelchair's speed is relatively slow. Meanwhile, when testing without load, the wheelchair can go fast. The power released at Pulse Width Modulation (PWM) 50, 100, and 255, respectively, has an average value of 23.37 W, 36.47 W, and 43.61 W. This data has different graphic results. The higher the PWM value, the greater the power released. Apart from that, the faster the wheelchair rotates, the more wasteful the battery is.